PENINGKATAN PEMAHAMAN KONSEP SISWA MELALUI MODEL PEMBELAJARAN IPA BERBASIS PHYSICS EDUCATION TECHNOLOGY-PROBLEM SOLVING - Florida Emmy Doloksaribu; Triwiyono Triwiyono (EDUSAINS, 2021)
IMPROVING STUDENT'S CONCEPT UNDERSTANDING THROUGH SCIENCE LEARNING MODEL  BASED OF THE PHYSICS EDUCATION TECHNOLOGY-PROBLEM SOLVINGAbstractThis study aims to determine the increase in understanding the concept of science material and the ability to experiment in a virtual context of energy and its changes in students of SMPN 13 Jayapura. This science learning model, PhET-Problem Solving on students needs to obtain models and teaching materials that were more effectively used. The learning model is validated based on the suitability of indicators and material, legibility, and the suitability of assignments and exercises at an average value of 85.75, which means it is very feasible to use. Participants consisted of a control class and an experimental class. The pretest and post-test results were analyzed based on the N-gain test; the experimental class dominated the high and medium categories at 30% and 70%, conventional class 27% and 46%. The implementation science learning model in context the energy context and its changes based on PhET-PS shows an increase in concept understanding and virtual experimental abilities. Based on the independent sample statistical test, it shows that there is a significant difference between the control class and the experimental class (sig.2-tailed <0.5). Student responses to the PhET-PS learning model were very positive.AbstrakPenelitian ini bertujuan untuk mengetahui peningkatan pemahaman konsep materi IPA dan kemampuan eksperimen secara virtual  konteks energi dan perubahannya pada siswa SMPN 13 Jayapura. Model pembelajaran IPA ini berbasis PhET-Problem Solving sesuai kebutuhan  siswa guna mendapatkan model dan bahan ajar yang lebih efektif digunakan. Model pembelajaran divalidasi berdasarkan kesesuaian indikator dan materi, keterbacaan, dan kesesuain tugas- tugas dan latihan pada nilai rata-rata sebesar 85,75 artinya sangat layak digunakan. Partisipan terdiri dari kelas kontrol dan kelas eksperimen. Hasil pretes dan postes dianalisis berdasarkan uji N-gain, pada kategori tinggi dan sedang didominasi kelas eksperimen yaitu 30% dan 70%, kelas konvensional 27% dan 46%.  Model pembelajaran IPA konteks energi dan perubahannya berbasis PhET-PS yang diimplementasikan menunjukkan terjadi peningkatan pemahaman konsep dan kemampuan eksperimen virtual. Berdasarkan uji statistik independent sampel menunjukkan terjadi perbedaan yang signifikan antara kelas kontrol dan kelas eksperimen (sig.2-tailed < 0,5). Tanggapan siswa terhadap model pembelajaran PhET-PS adalah sangat positif.